Development Optimization and Cytotoxicity Evaluation of Glyburide Loaded Nanostructured Lipid Carriers - M, Ashwini; Sudheer, Preethi; Sogali, Bharani S.; R, Chandramouli (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim/Background: In the present study Glyburide, a hypoglycaemic agent was loaded into nanostructured lipid carriers. The solid and liquid lipid concentrations within the formulation were optimized using central composite design with two centre points augmented with a cluster of axial and factorial points (star points). Materials and Methods: The responses particle size and drug entrapment were used to optimize the concentration ratio by central composite design. The nanostructured lipid carriers were prepared by melt dispersion technique and the optimized formulations were evaluated for various physicochemical, morphological, histological and toxicity parameters. Results: Central composite design paradigm was successful in defining the best lipid concentrations. Scanning electron microscopy and atomic force microscopy revealed the morphological characteristics of the nanoparticle. The outcome of X- ray diffraction confirmed the molecular dispersibility of the drug in the lipid matrix. Histopathological study conceded the scope of formulating a transdermal delivery system using the optimized nano carrier. Cell viability study in baby hamster kidney-21 cell culture substantiated the non-toxicity of the nanoparticles. Conclusion: Study construed the suitability of the design model in optimization and assessment of the impact of the concentration of solid lipid as well as liquid lipid on the responses particle size and drug entrapment efficiency.
Keywords: Glyburide; Central composite design; MTT assay; Cell viability study; BHK -21 cell-line; Histopathological study